2018
DOI: 10.3390/su10124503
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Effects of Public Service Facilities Accessibility on Housing Prices: A Case Study of Xi’an, China

Abstract: The premium effect of public service facilities on the housing market is a critical determinant of housing prices, leading to the competition of different social groups in the housing market and fueling spatial inequality. Taking Xi’an, China as a case in point, this study uses Geographic Information System (GIS) to describe the spatial distribution pattern of housing prices and urban public service facilities. Using the mixed geographically weighted regression model (MGWR) and the geographical detector model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…Housing has been the most dominant research subject among all types of real estate properties in the urban and transportation literature [17,24,29,30]. Studies exclusively on warehouse rent were rare in the past, but several studies on industrial properties do exist.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Housing has been the most dominant research subject among all types of real estate properties in the urban and transportation literature [17,24,29,30]. Studies exclusively on warehouse rent were rare in the past, but several studies on industrial properties do exist.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They identified four major influence factors on housing price with significant spatial variabilities: Distance to the inner ring, distance to hospitals, bus density, and distance to subway stations. Lan et al [24] applied the MGWR and the geographical detector (GD) to analyze the spatial effect of accessibility to public service facilities on housing prices based on the case of Xi'an, China.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For facilities in case II that are laid out according to large administrative units, their capitalisation effects are considerable. Similarly, cultural facilities [43,57] and sports facilities [43] as well as shopping malls [60] were found that they have notable value-added effects on surrounding houses.…”
mentioning
confidence: 99%
“…Municipal parks and river-views [26,46] as high-quality and scarce landscape endowments, make an obvious value-added effect on houses in the vicinity. Lan et al [57] also deemed that basic education is a basic necessity, and culture, sports and finance are a higher-level of needs. The current study responds to the conclusions of previous researches, which partially explain the correctness of the current study.…”
mentioning
confidence: 99%